Design and Validation of a Classroom Observation Instrument to Evaluate the Quality of Mathematical Activity from a Gender Perspective - Espinoza-Salfate, L; Barbe-Farre, J; Marquez-Salinas, F (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study aimed to design and validate an instrument as a guideline for classroom observation and analysis of teaching–learning process in mathematics. The instrument considers 3 dimensions and 16 subdimensions with a gender perspective. A content validity process by eight expert judges is presented, built from a dialectical work between theory and empirical evidence from more than 100 classes observed and recorded on video from 19 educational centers. The degree of agreement between experts was determined with Fleiss Kappa and Kendall coefficients. Experts’ judgement scored each dimension from 1 to 3. Globally, an almost perfect strength of agreement was obtained in 6 of 16 dimensions with (Formula presented.), and in the other 10 dimensions, a strength of agreement was obtained between moderate and almost perfect, (Formula presented.). Fleiss Kappa coefficients were highest in relevance and clarity, (Formula presented.) = 0.425, 95% CI [0.344, 0.506], p < 0.001 and, (Formula presented.) = 0.461, 95% CI [0.375, 0.548], p < 0.001, respectively. Moreover, the degree of clarity, coherence, sufficiency, and relevance was statistically moderately agreed upon in their assessments, with an overall Kendall’s W = 0.489, p < 0.001. © 2023 by the authors.